Increased incidence of systemic serious viral infections in patients with inflammatory bowel disease associates with active disease and use of thiopurines. Issue 3 (1st April 2020) - Wisniewski, Andrew; Kirchgesner, Julien; Seksik, Philippe; Landman, Cécilia; Bourrier, Anne; Nion‐Larmurier, Isabelle; Marteau, Philippe; Cosnes, Jacques; Sokol, Harry; Beaugerie, Laurent; ,; Arrivé, Lionel; et al.
Abstract : Background: The magnitude and drivers of the risk of serious viral infections in Inflammatory Bowel diseases (IBD) are unclear. Objective: The objective of this study was to assess the incidence and risk factors for systemic serious viral infections in IBD patients. Methods: Using MICISTA, a database detailing prospective characteristics and complications of IBD, we identified patients that were followed for IBD in 2005–2014 outside the context of organ transplantation, HIV infection or chronic viral hepatitis. We estimated incidences of systemic serious viral infections, defined by the need for hospitalization or permanent organ damage. Standardized incidence ratios (SIRs) were calculated using the French hospital database. We performed a case‐control study nested in MICISTA for assessing the role of exposure to IBD drugs and IBD clinical activity in the risk of developing infection. Results: We identified 31 patients with serious viral infections among 2645 patients followed for 15, 383 person‐years. We observed 13 cases of cytomegalovirus, 10 Epstein–Barr virus, 5 varicella zoster virus and 3 herpes simplex virus infections. No deaths occurred. The incidence rate of infections in patients with IBD was 2.02/1000 person‐years, and the SIR was 3.09 (95% confidence interval (CI), 1.98–4.20; p  = 0.0002) in the study population. By multivariate analysis, increased risk of infection was associated with exposure to thiopurines (odds ratio (OR), 3.48; 95% CI, 1.36–8.90; p  = 0.009), and clinically active IBD at onset of infection (OR, 3.35; 95% CI, 1.23–9.23; p  = 0.02). Conclusions: The incidence of systemic serious viral infections in patients with IBD is tripled compared to general population. Clinically active IBD and exposure to thiopurines are the main drivers of the risk.